THE CONTRIBUTION OF TEACHER EDUCATION TO LITERACY INSTRUCTION QUALITY IN PRIMARY SCHOOLS - Elly Purwanti (Indonesian Journal of Education and Youth Development, 2025)
This study analyzes the relationship between teacher education and the quality of literacy instruction in primary schools. Employing a qualitative research design with an extensive literature review and case study analysis, the study finds that teacher education contributes significantly to improved student literacy outcomes. Effective programs feature strong pedagogical foundations and adequate practicum experiences. However, the research also identifies critical gaps, including a lack of training in differentiation and literacy interventions. These findings highlight the need for curriculum reforms that focus on practical training, continuous professional development, and the standardization of teacher education programs.